Evolution of copper oxide nanoneedle mesh with subtle regulated lyophobicity for high efficiency liquid separation. Issue 3 (20th December 2017) - Qiu, Mengna; Wang, Nü; Cui, Zhimin; Liu, Jing; Hou, Lanlan; Liu, Jingchong; Hu, Rongjun; Zhang, Hailong; Zhao, Yong
Abstract : The relationship between copper oxide nanostructures and lyophobicity has been systematically researched for the design of lyophobic copper materials. Abstract : Metallic engineering materials with facile tunable wetting performances are important for diverse applications. Here, copper oxide nanoneedle meshes with regulable lyophobicity are fabricated through the oxidation of copper meshes and surface modification. The continuous structural evolution of the copper oxidation process is systematically investigated. After surface modification, the wettability of the meshes show a good correlation to the structural features. This systematic research provides a reference for the goal-directed, precise design of copper engineering surface structures with controllable wettability.